👤

Directions: Transform the following quadratic equation into vertex form.
1. f(x) = x² + 4x + 5
4. f(x) = x² – 2x + 6
2. f(x) = 2x² – 10x + 6
5. f(x) = 4x² + 3x + 2
3. f(x) = 3x² – 4x + 1​


Sagot :

Answer:

1. y= (x + 2)^2 + 1

4. y= (x - 1)^2 + 5

2. y= 2(x - 5/2)^2 - 13/2

5. y= 4(x + 3/8)^2 + 23/16

3. y= 3(x - 2/3)^2 - 1/2

Step-by-step explanation:

hope it helps:)

pa brainliest

marunong ka bang magbilang?

hehe

  • [tex]f(x) = (x + 2)^{2} + 1[/tex]

  • [tex]f(x) = {(x - 1)}^{2} + 5[/tex]

  • [tex]f(x) = 2 {(x - \frac{5}{2})}^{2} - \frac{13}{2} [/tex]

  • [tex]f(x) = 4 {(x + \frac{3}{8}) }^{2} + \frac{23}{16} [/tex]

  • [tex]f(x) = 3 {(x - \frac{2}{3})}^{2} – \frac{1}{3} [/tex]